Results Monitoring in Health, Nutrition, and Population : The Experience of the Africa Region 2009/2010 - Martin, Gayle H.; Loevinsohn, Benjamin; Saito, Eriko (World Bank, Washington, DC, 2013)
The Bank's shareholders and stakeholders are increasingly demanding better accountability for results and progress toward achieving the Millennium Development Goals (MDGs). In response, the various reforms and initiatives toward an enhanced results orientation have increased in prominence, yet actual progress has lagged. The purpose of the study was to provide an assessment of results monitoring in the Africa Health, Nutrition and Population (HNP) portfolio. The report focuses on results monitoring and less on evaluation, because tracking results is one of the most basic requirements to improve accountability for results and a key precursor to evaluation. The study combined quantitative and qualitative techniques. The quantitative analysis assessed the design of results frameworks, its implementation and use in all 52 active Africa HNP projects; the qualitative assessment surveyed the experiences of task team leaders (TTLs) and aimed to identify some incentives, as well as some innovative and strategic actions, to improve results monitoring. Only 17 percent of data collection plans were mostly, implemented and those projects with data were more likely to discuss progress and make reference to data in deciding on ratings. The extent to which data collection plans were implemented had a direct relationship with the number of indicators in the design. The implementation of data collection plans also determined the extent to which there is any discussion of results in the Implementation Status and Results Report (ISR) and use of evidence used to underpin the ratings used to track project performance. Although assessments of capacity in results monitoring and evaluation were conducted in only a quarter of projects, most projects planned to support capacity building. There was however deficiencies in the extent to which the planned support were executed.